Cembranoids Content of Soft Coral Sarcophyton from Acidified Environment at Volcano Island, Indonesia - Hedi Indra Januar; Neviaty Putri Zamani; Dedi Soedharma; Ekowati Chasanah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
Cembranoid content in soft coral is known as a chemotype that relate with genotype and environment. This research aimed to characterize the cembranoid Sarcophyton soft coral from the reef that acidified by CO2 volcanic vents (pHT 7.8) at Volcano Islands waters, Banda-Neira (Indonesia), as a means of predicting the future impact of ocean acidification to the genetic diversity of Sarcophyton soft coral. 30 random colonies were taken, combined, and extracted with ethanol. Cembranoid isolation and identification had been done by high performance liquid chromatography and spectroscopic techniques. Results of the study found sarcophytol derivatives (sarcophytol A, 11,12-epoxy sarcophytol A, sarcophytol B, and sarcophytol M) as the only chemotype in the sample. This may suggest low genetic diversity in the observed Sarcophyton sample. Therefore, it may suggest that even soft coral is known to be resilient to future acidification pressures, the genetic diversity or the production of diverse cytotoxic metabolite may be hampered due to ocean acidification in future climate change adaptation.